Disain Antena Mikrostrip Array Tiga Band untuk Aplikasi WiFi dan WiMax - Abrianto, H. Heru; Irmayani Husein Mukdien (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
In this research, a 1x2 circular patch microstrip array antenna with feeding line is made which can be used on WiFi and WiMax which work at frequencies of 2.4, 3.7 and 5.8 GHz. This antenna design uses Ansoft HFSS software. Where the simulation results at a frequency of 2.4 GHz obtained a return loss value of -22.28 dB, -19.03 dB at 3.7 GHz and -14.94 dB for 5.8 GHz, VSWR 1.17 for 2.4 GHz, 1.25 at 3, 7 GHz and 1.43 for 5.8 GHz.Gain is 1 dB and directivity is 2,33 dB. The simulation results show that the parameters meet the minimum standard of the performance of an antenna, the Return Loss (RL)<-10 dB for 5.8 GHz, VSWR<2. Therefore, this antenna is suitable for use for WIFI and WLAN applications